If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + -4) = 0 Reorder the terms: (3 + x)(x + -4) = 0 Reorder the terms: (3 + x)(-4 + x) = 0 Multiply (3 + x) * (-4 + x) (3(-4 + x) + x(-4 + x)) = 0 ((-4 * 3 + x * 3) + x(-4 + x)) = 0 ((-12 + 3x) + x(-4 + x)) = 0 (-12 + 3x + (-4 * x + x * x)) = 0 (-12 + 3x + (-4x + x2)) = 0 Combine like terms: 3x + -4x = -1x (-12 + -1x + x2) = 0 Solving -12 + -1x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-3 + -1x)(4 + -1x) = 0Subproblem 1
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-3, 4}
| 43-1296-125= | | 9.9a+9.63=-88.38 | | y=1.2-3+3 | | y=1.3-3+3 | | 10-7x=50-42x | | 5x+7=6-(6x-3) | | x^2-y^2-2x+18y-180=0 | | 45a^4b^3-90a^3b/15a^2b | | 2x^3-10x^2+x-5=0 | | d=32+0.3 | | 9n-3=48 | | (5x-3)=12 | | 5.14+x=7 | | 51/7+x=7 | | 17=11-2x | | 9.2x=33.12 | | 3*4x^3= | | 0=x^2+15x-100 | | 2(2)+y=2 | | 39-12=48 | | 14(x-5)=112 | | (9x^2-6x+1)*(3x+2)=0 | | X-1=6.13 | | -25-3x=11x-7 | | 5x-2(x-5)=-4+5x+8 | | 2x+(-1/2x-1)=2 | | -9y=2.52 | | 26(-17)+15(-22)= | | 2n+12=36 | | (5v-7)*(2v+9)=0 | | 9x-4=293 | | -7-6x=14+9x |